Architettura e immagine femminile: alla ricerca di una ricerca - Ceriani Sebregondi, Giulia (Il sogno della farfalla, 2008)
This work analyses the relationship between architecture and the female image, starting from questions such as “Are there important female architects? The fact that there are so few depends exclusively on social conditioning? Is it possible to tell whether a building was designed by a man or a woman? Does a female architecture, as well as a male architecture, exist? If there are any differences, what gives rise to them?”. The research is developed firstly through a historical review of the main female architects of the 1900s, then through some striking examples of female clients of contemporary architecture, to then concentrate on some aspects of architectural theory of the Modern movement and of Postmodernism, linked to the theme of “gender”. The author proposes, lastly, to continue the research not so much in terms of the double binomial male/rational -female/irrational, but in terms of on the conscious/unconscious relationship, and therefore link the activity of architecture to this second element, following the theory that to make art it is necessary to recreate the way of thinking-imagining characteristic of the first year of life. In this way, perhaps, if there is no scission with physical reality, we could see the emergence of architectures in which “female” and “male” characteristics are recognizable, in that they are linked to one’s personal identity and the relationship with other human beings.